Affective Assessment in Online English Classroom: How does It Work? - Maisarah, Ira; Arsyad, Safnil; Sofyan, Dedi (English Education : English Journal for Teaching and Learning, 2023)
This study discusses the challenging of assessing affective in English online classes at a junior high school in Bengkulu city. The method used was mix method with a questionnaire and structured interview through a google form. There are fifty English teachers who became the informant in this study. The findings showed that English teachers face challenges in assessing affective. Moreover, the assessment cannot be done concurrently, because of the limited time during online learning. Despite the affective assessment-based practice being the main assessment as the goal of learning, the way how to assess was still needed to be improved in the future.